The Role of Cognitive Ease in the Utilization and Preparation of Accounting Information in SMEs - Ridhawati, Rini; Suryantara, Adhitya Bayu; Rizki, Novia (E-Jurnal Akuntansi; Vol 34 No 11 (2024)DO - 10.24843/EJA.2024.v34.i11.p02, 2024)
Micro,  Small,  and  Medium  Enterprises  (MSMEs)  play  a  crucial  role  in  Indonesia’s economy,  particularly  in  job  creation  and  reducing  unemployment.  Despite  their significant contribution, MSMEs face a persistent challenge in the limited preparation of financial reports, which hampers their ability to assess and ensure financial performance with certainty. Addressing this issue, this study investigates the influence of cognitive ease—conceptualized through repeated experience and avoidance of cognitive strain—on the utilization and preparation of accounting information by MSMEs. The research focuses  on  400  MSMEs  in  Mataram  City,  employing  the  Partial  Least  Square  (PLS) method  with  SmartPLS  4.0  for  data  analysis.  The  findings  reveal  that  repeated experience exerts a significant positive effect on both the utilization and preparation of accounting   information.   In   contrast,   the   avoidance   of   cognitive   strain   does   not significantly  impact  the  utilization  of  accounting  information  but  demonstrates  a significant negative effect on its preparation. These results underscore the critical role of repeated  experience  in  improving  MSMEs’  accounting  practices,  suggesting  that consistent  engagement  with  accounting  processes  enhances  their  effectiveness.  The study highlights the need for targeted interventions to bolster cognitive familiarity with accounting tasks, paving the way for more reliable financial reporting among MSMEs.